2018
DOI: 10.1111/poms.12789
|View full text |Cite
|
Sign up to set email alerts
|

Location and Emergency Inventory Pre‐Positioning for Disaster Response Operations: Min‐Max Robust Model and a Case Study of Yushu Earthquake

Abstract: P re-positioning emergency inventory in selected facilities is commonly adopted to prepare for potential disaster threat. In this study, we simultaneously optimize the decisions of facility location, emergency inventory pre-positioning, and relief delivery operations within a single-commodity disaster relief network. A min-max robust model is proposed to capture the uncertainties in both the left-and right-hand-side parameters in the constraints. The former corresponds to the proportions of the pre-positioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 42 publications
0
87
0
2
Order By: Relevance
“…With the deepening of exploration, research flourished. The study of emergency resource allocation has slowly extended into the field of natural disasters [27][28][29][30], hazardous chemical accidents [31], railway emergencies [32], and so on. For instance, Tzeng et al established a scheduling model with the minimal rescue time, the lowest rescue costs, and the highest satisfaction [29].…”
Section: The Allocation Of Emergency Resourcesmentioning
confidence: 99%
“…With the deepening of exploration, research flourished. The study of emergency resource allocation has slowly extended into the field of natural disasters [27][28][29][30], hazardous chemical accidents [31], railway emergencies [32], and so on. For instance, Tzeng et al established a scheduling model with the minimal rescue time, the lowest rescue costs, and the highest satisfaction [29].…”
Section: The Allocation Of Emergency Resourcesmentioning
confidence: 99%
“…escuelas). Propuestas de este estilo se encuentran en [24]- [27]. En [43], trabajo que aborda el "preposicionamiento integrado" que combina los objetivos de operaciones de respuesta a emergencias y operaciones de largo plazo lideradas por el Alto Comisionado de Naciones Unidas para los refugiados -UNHCR por sus siglas en inglés-, también se propone un rediseño de la red existente, partiendo de infraestructura potencial que habría que ser construida.…”
Section: Modelamiento Matemático En Logística Humanitariaunclassified
“…Desde el punto de vista de los esfuerzos de planeación a desastres basados en programación matemática, es importante mencionar que si bien en la literatura de logística humanitaria, diferentes autores han abordado la localización de instalaciones, el preposicionamiento del inventario (e.g. [22]- [27]). El factor común de estas publicaciones es que el diseño y configuración de la red "complementaria" tiene origen en infraestructura no existente o en locaciones "potenciales" que no pertenecen a redes integradas y no contemplan, por tanto, alternativas como la adaptación de redes ya operantes.…”
Section: Introductionunclassified
“…Similarly, based on the death rate for integrated emergency system in Figure 4, the expected benefits ℎ when medical departments take action in time with no fastpreliminary response are computed as in (7).…”
Section: Benefits Of Integrated Emergency Response Systems Wherementioning
confidence: 99%
“…Extensive researches have been conducted on the management of emergency preparation, response, and recovery [6]. In emergency preparation phase, researches demonstrated that optimal decisions for location and inventory of emergency materials have a direct impact on the responsiveness and capacity of emergency response [7][8][9]. The distribution and transportation of emergency resources are the main decisions in the process of emergency response [10,11].…”
Section: Literature Reviewmentioning
confidence: 99%